Academic Entrepreneurship Ecosystems: Systematic Literature Review and Future Research Directions - Correia, Maria Patrocínia (2024)
Research on the entrepreneurship ecosystem, based on different data and scales, limits the acceptance of a single definition. This conceptual limitation and the still recent research and higher education institutions have come to be seen as ecosystems associated with entrepreneurship. The aim of this study is to contribute to the field of knowledge, identify current and emerging thematic areas and trends and reveal the scientific roots of research on entrepreneurial ecosystems and their relationship with higher education institutions. A bibliometric analysis was developed to analyse a final sample of 110 articles published between 2011 and 2022. In order to develop the analysis, Bibliometrix R-Tool was used and the metadata of two databases (Web of Science and Scopus) was retrieved and merged. The software creates a reference co-citation's map, which allowed emphasize the state of the art and indicate three thematic clusters: (i) the importance of the higher education context for the entrepreneurial ecosystem, (ii) the evolution and challenges of entrepreneurship education and (iii) academic entrepreneurship ecosystems. The paper concludes by suggesting future research focused on the importance of building an integrated approach to entrepreneurial ecosystems and higher education institutions on a context regional scale.